PELATIHAN PENINGKATAN PENGUASAAN KOSA KATA BAHASA INGGRIS DENGAN TEKNIK MENYANYI DAN MENGGUNAKAN FLASH CARDS BAGI SISWA-SISWI SDN 1 KESIUT - Widiastuti, Ni Made Ayu (Buletin Udayana Mengabdi; Vol 19 No 2 (2020): Buletin Udayana Mengabdi, 2020)
The English trainings given to the students in the 4 th and 5 th grades in SDN 1 Kesiut aims at finding out the topics of the English lessons in their English books in order to know the vocabulary given in the training, and describing the results of the training by using flash cards and singing technique. The trainings were given four times during the program, with the duration of 1,5 hours on each meeting and each class. The topics in the 4 th grade English book are “I buy hat’, “It’s raining today”, “Went to Borobudur”, and “Let’s have fun”, and in the 5 th grade are “I am cooking”, “We are at school”, “I like pizza”, and “My red cap”. The results show that the students are able to enhance the mastery of the English vocabulary after the training.  The use of flash cards improved the vocabulary  mastery between 19% - 47% (class 4), and 1% - 20% (class 5). Moreover, by applying singing technique, the improvement shown by the 4 th grade students is approximately 16% - 48 %, and it is around 9% - 38% shown by the 5 th grade students. Key words : training, improvement, English vocabulary, flash cards , singing